Reflective Synergy: A Research Model for Collaborative Inquiry - Craig A. Mealman; Randee Lipson Lawrence (Adult Education Research Conference, 2002)
A theoretical model for collaborative inquiry as a research methodology in adult education is presented in this paper. The authors discuss the elements of the model along with their lived experience through its development.